2006
DOI: 10.1007/bf02973914
|View full text |Cite
|
Sign up to set email alerts
|

In vivo pharmacokinetics, activation of MAPK signaling and induction of phase II/III drug metabolizing enzymes/transporters by cancer chemopreventive compound BHA in the mice

Abstract: Phenolic antioxidant butylated hydroxyanisole (BHA) is a commonly used food preservative with broad biological activities, including protection against chemical-induced carcinogenesis, acute toxicity of chemicals, modulation of macromolecule synthesis and immune response, induction of phase II detoxifying enzymes, as well as its undesirable potential tumor-promoting activities. Understanding the molecular basis underlying these diverse biological actions of BHA is thus of great importance. Here we studied the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Recent findings suggest that the cis-acting regulatory element and the antioxidant response element (ARE)/ electrophile response element (EpRE), play important roles in the transcriptional regulation of phase II genes, such as quinone oxidoreductase (EC 1.6.5.2), GST (EC 2.5.1.18) and UGT, by phenolic antioxidants (Kong et al, 2001;Rushmore & Kong, 2002;Xu et al, 2005). Several ARE/EpRE-binding proteins have been identified, including the members of basic leucine zipper transcriptional factor family, nuclear factor erythroid 2-related factor 1, 2 (Nrf1, Nrf2) and small Maf proteins (Buetler et al, 1995;Hu et al, 2006). Nrf2 is the most likely transcriptional factor involved in the transcriptional activation of ARE-mediated phase II genes by a phenolic antioxidant in Nrf2À/À mice studies (Maher & Yamamoto, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings suggest that the cis-acting regulatory element and the antioxidant response element (ARE)/ electrophile response element (EpRE), play important roles in the transcriptional regulation of phase II genes, such as quinone oxidoreductase (EC 1.6.5.2), GST (EC 2.5.1.18) and UGT, by phenolic antioxidants (Kong et al, 2001;Rushmore & Kong, 2002;Xu et al, 2005). Several ARE/EpRE-binding proteins have been identified, including the members of basic leucine zipper transcriptional factor family, nuclear factor erythroid 2-related factor 1, 2 (Nrf1, Nrf2) and small Maf proteins (Buetler et al, 1995;Hu et al, 2006). Nrf2 is the most likely transcriptional factor involved in the transcriptional activation of ARE-mediated phase II genes by a phenolic antioxidant in Nrf2À/À mice studies (Maher & Yamamoto, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the inhibitory effect of aloin on DSS-induced colonic inflammation may be partly due to the inhibition of the ERK, JNK and p38 signaling pathways. Recently, Hu et al (2006) reported that the MAP kinase pathways may play an important role in early signaling events leading to the regulation of gene expression of phase II enzymes, including UGTs. We have previously demonstrated that aloesin is transformed to aloesin glucuronides/sulfates during intestinal absorption by UGT enzymes (Park et al 2009b), indicating that aloesin-regulated MAP kinase activity may also be involved in the absorption of aloesin.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of P-gp and MRP1 appears to play a major role in the development of resistance, although this varies with cell type and the specific drugs concerned. Recent data indicate that Phase III detoxification transporters may be up-regulated in concert with Phase I and/or Phase II enzymes [10][11][12][13]. Thus, the system that improves defense against toxic compounds and aids in cancer prevention is the same as that found to be up-regulated in a variety of hematological and solid tumors expressing clinical drug resistance.…”
Section: Introductionmentioning
confidence: 99%